Evaluasi Dampak Game Based Learning dalam Era Pendidikan Digital: Systematic Literature Review - Syaiful Indra; Sujadi, Eko; Putra, Hastha Purna (Al-Riwayah : Jurnal Kependidikan, 2025)
The future of education faces complex challenges related to technology adaptation, curriculum relevance, and educational accessibility. An innovative approach that continues to gain momentum is Game-Based Learning (GBL) and gamification, which aim to enhance student engagement, motivation, and learning outcomes through interactive game elements. This study investigates the GBL approach and its impact within the context of digital education. The method used is a Systematic Literature Review (SLR), analyzing recent literature from 2023 to 2024. The findings indicate that GBL incorporates advanced technologies such as Virtual Reality (VR), Augmented Reality (AR), and artificial intelligence (AI)-powered interactive platforms. These technologies have proven effective in supporting project-based learning, promoting digital literacy, and personalizing educational experiences to meet individual student needs. Furthermore, gamification—using narrative elements, challenges, and rewards—has been shown to increase curiosity and deepen engagement in the learning process. In conclusion, GBL and gamification present significant potential to foster dynamic, interactive, and inclusive learning environments. When designed effectively, these methods can not only improve learning motivation but also equip students with the skills necessary to tackle the challenges of the digital age. Further research is essential to address implementation obstacles and ensure the optimal integration of these approaches into the broader education system